(3NWhI CSGSjI dehGcHI GdEbJUGO GdYGdejs - (3eMeO cGed(B, (3OQhjTs ([(3O(B.(3e(B.]:s [(3O(B.(3f(B.],s)
(3VQjHI GdbjeI GdeVGaI NWhI CSGSjI dehGcHI GdEbJUGO GdYGdej(B- (3GJaGb GdTQGcI GdCQhQHjI JMbjb GdefGaSI aj GdEbJUGO GdYGdej(B- (3GdEJaGbjI GdYGeI dJLGQI GdNOeGJ (B((3GdLGJ(B).s
Keywords: (3GdEbJUGO GdYGdej(B- (3GdVQGFHs; (3GdVQGFH(B- (3GdbjeI GdeVGaI s